Analisis Kadar Tanin Dalam Buah Mangrove Avicennia marina Dengan Perebusan Dan Lama Perendaman Air Yang Berbeda - Nirwani Soenardjo; Endang Supriyantini (Jurnal Kelautan Tropis, 2017)
Mangrove fruit has the potential to be developed as a potential food source, but the presence of toxins in the fruit are considered harmful if consumed in the long run. Therefore, research needs to be done to eliminate or reduce the levels of toxins in the mangrove fruit, in order to increase the potential of the mangrove plants. The poison is in the mangrove fruit tannins. One alternative to reduce the levels of toxins in the fruit of the mangrove scrub with ash and water immersion.The purpose of this study was to determine the effect of treatment of ash powder content and the duration of water immersion on fruit tannin content of mangrove Avicennia.marina.The treatment was a long 24 hours of water immersion 4 times change of water (6 hours), 48 hours 8 times a change of water (6 hours), and 72 hours 12 times a change of water (6 hours). The results showed that treatment long soaking water to give a significant influence (P <0.05) toward decreased levels of mangrove Avicennia marina fruit tannins. Treatment a long 72 hours of water immersion 12 times a change of water (6 hours) to reduce levels of tannins by 28.80%.  Buah mangrove mempunyai potensi untuk dikembangkan menjadi sumber pangan yang potensial, akan tetapi dalam buahnya mengandung tannin . Tanin merupakan zat alami yang dihasilkan oleh buah mangrove yang memberi rasa getir. Oleh karena itu, perlu dilakukan penelitian untuk mengurangi kadar tannin dalam buah mangrove. Tujuan penelitian ini adalah untuk menganalisis pengaruh perlakuan  lama waktu perendaman air terhadap kadar tanin buah mangrove A.marina.Perlakuan  lama perendaman air 24 jam 4 kali pergantian air (6 jam), 48 jam 8 kali pergantian air (6 jam), dan 72 jam 12 kali pergantian air (6 jam). Hasil penelitian menunjukan bahwa perlakuan lama perendaman air memberikan pengaruh yang nyata (P < 0.05) terhadap penurunan kadar tanin buah mangrove Avicennia marina. Perlakuan lama perendaman air 72 jam 12 kali pergantian air (6 jam) menurunkan kadar tanin  sebesar 28,80 %